2020
DOI: 10.1002/ctm2.190
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lncRNA MALAT1 by betulinic acid inhibits hepatocellular carcinoma progression by targeting IAPs via miR‐22‐3p

Abstract: Betulinic acid (BA) is a natural product extracted from a broad range of medicinal and edible herbal plants. Previous studies showed that BA induces cell death in tumors derived from multiple tissues; however, the underlying mechanism remains obscure. The present study aimed to study the effects of BA on autophagy and apoptosis of hepatocellular carcinoma (HCC). Human HCC cell lines and orthotopic HCC implanted mice were employed to examine the BA‐induced tumor suppression; RT 2 long non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…It has been reported that BA also can induce cell autophagy, which results in either cell death or survival ( Li et al, 2019 ; Chen et al, 2020 ). Increasing evidence highlights that cancer cells have the ability to harness autophagy to thrive ( Galluzzi et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that BA also can induce cell autophagy, which results in either cell death or survival ( Li et al, 2019 ; Chen et al, 2020 ). Increasing evidence highlights that cancer cells have the ability to harness autophagy to thrive ( Galluzzi et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemicals are biologically active compounds isolated from plants or herbs, which are recognized as potent anticarcinogenic agents ( Yin et al, 2017 ; Ng et al, 2018 ; Chen et al, 2020 ). Betulinic acid (BA, (3β)-3-hydroxyl-lup-20 (29)-en-28-oic acid, the chemical structure of BA shown in Figure 9G ) is a naturally lupane-structured pentacyclic triterpenoid that is mainly widespread in white-barked birch trees ( Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For these inhibitors, the main research report is to inhibit the activity of SREBP-1 as a tool in metabolism-related research. Betulin can exert anti-tumor activity in HCC (78)(79)(80). Pseudoprotodioscin and Fatostatin have been less studied in HCC, but it has also been clearly reported in other tumor types (81)(82)(83)(84).…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis Associated Lung Adenocarcinoma Transcript 1 (MALAT1) is one of the most widely studied lncRNAs in cancer therapy. lncRNA MALAT1 was found to play an oncogenic role in the occurrence and development of HCC and act as a proto-oncogene to regulate the expression of apoptosis inhibitor IAPS [ 128 ]. MALAT1 can act as the ceRNA of miR-22-3p to cause the abnormal expression of the target gene inhibitor of apoptosis proteins (IAPs) [ 129 ].…”
Section: The Potential Of Lncrna Related Cernet As Therapy Target In Hccmentioning
confidence: 99%